Ground Surface Deformation in the Hanging Wall of the Jinshandian Underground Iron Mine in China - Wang, Tianlong; Chen, Congxin; Xia, Kaizong; Zhang, Chuqiang; Wang, Yue; Liu, Xuanting (Frontiers in Earth Science, 2022)
When sublevel caving is used in metal mines, the stress state in the rock mass that initially existed around the mined-out area will be destroyed. This will lead to the rock strata deforming and moving and also, potentially, to large-scale collapse and cracking of the ground surface. Such ground surface deformation can cause significant damage to buildings and other structures. Therefore, it is very important to study the mechanism responsible for this ground surface deformation so that methods can be devised to protect the mine’s production facilities as well as the property and safety of nearby residents. In this study, the mechanism responsible for the surface deformation of the hanging wall in the eastern part of the Jinshandian iron mine was investigated by analyzing monitoring data collected in situ on the surface (from 2008 to 2020) and other related information (occurrence of surface cracking and collapse and geological conditions). The results show that the ground surface deformation can be divided into four stages (initial, creep, slow, and accelerating deformation stages). A flexural toppling failure model is proposed to account for the surface deformation. The model suggests that large-scale deformation of the ground surface at the hanging wall occurs due to the combined effect of in situ ground stress, occurrence of steep dip discontinuities and faults, the dips and strikes of the two parallel orebodies, and underground mining activity. Furthermore, the surface deformation can be divided into six regions corresponding to caved, rapidly-accelerating deformation, slowly-accelerating deformation, acceptable deformation, slight deformation, and no deformation zones. In the rapidly-accelerating deformation zone, the ratio of the horizontal to vertical displacement is greater than 1 and some major cracks can be found. Large-scale cracks begin to form when the horizontal velocity of the ground surface is greater than 1 mm/day.